Development Of Booklets To Facilitate Student Discipline At SMA Negeri 2 Seluma - Meza Hadevi Meza Hadevi (Universitas Muhammadiyah Enrekang, 2026)
This study aims to develop a learning media in the form of a booklet based on the character value of discipline for 11th grade high school students. The background of the research is based on the low level of student discipline and the limited biology learning media that integrate character values ​​in teaching materials. The research problem is focused on the level of validity and practicality of the booklet developed to improve conceptual understanding while strengthening students' character of discipline. The method used is Research and Development (R&D) with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. The Define stage is carried out through analysis of needs, student characteristics, and curriculum. The Design stage includes designing the content structure, integration of discipline values, and visual design of the booklet. The Develop stage includes product preparation, validation by material experts, media experts, and language experts, and revisions based on validator suggestions. The Disseminate stage is carried out through a limited trial to assess the practicality of using the booklet in learning. The research instruments are validation sheets and teacher and student response questionnaires with a Likert scale. The trial subjects consist of experts, one biology teacher, and 60 11th grade students. The results showed that the booklet was categorized as very valid, with an average percentage above 85%. The teacher's practicality test reached 95%, while the student response averaged 90%. Thus, the booklet was declared very valid and practical for use as a learning support medium. Abstrak Penelitian ini bertujuan mengembangkan media pembelajaran berupa booklet berbasis nilai karakter disiplin untuk siswa kelas XI SMA. Latar belakang penelitian didasarkan pada rendahnya tingkat kedisiplinan siswa serta terbatasnya media pembelajaran biologi yang mengintegrasikan nilai karakter dalam materi ajar. Permasalahan penelitian difokuskan pada tingkat validitas dan kepraktisan booklet yang dikembangkan untuk meningkatkan pemahaman konsep sekaligus penguatan karakter disiplin siswa. Metode yang digunakan adalah Research and Development (R&D) dengan model pengembangan 4D yang meliputi tahap Define, Design, Develop, dan Disseminate. Tahap Define dilakukan melalui analisis kebutuhan, karakteristik siswa, dan kurikulum. Tahap Design mencakup perancangan struktur isi, integrasi nilai disiplin, serta desain visual booklet. Tahap Develop meliputi penyusunan produk, validasi oleh ahli materi, ahli media, dan ahli bahasa, serta revisi berdasarkan saran validator. Tahap Disseminate dilakukan melalui uji coba terbatas untuk menilai kepraktisan penggunaan booklet dalam pembelajaran. Instrumen penelitian berupa lembar validasi dan angket respon guru serta siswa dengan skala Likert. Subjek uji coba terdiri atas para ahli, satu guru biologi, dan 60 siswa kelas XI. Hasil penelitian menunjukkan bahwa booklet memperoleh kategori sangat valid dengan persentase rata-rata di atas 85%. Uji kepraktisan oleh guru mencapai 95%, sedangkan respon siswa menunjukkan rata-rata 90%. Dengan demikian, booklet dinyatakan sangat valid dan praktis digunakan sebagai media pendukung pembelajaran